Traditional Communication in Modern Organizations: A Study of Protocol Communication of the Padang Lawas Utara Regency - Syafruddin Ritonga Ritonga; Nina Siti Salmaniah Siregar; Isnaini Isnaini; Wenggedes Frensh (International Journal of Artificial Intelligence Research, 2022)
This study aims to analyze the frequent errors of protocol officers in carrying out activities, which of course affect the image of the North Padang Lawas Regency government. errors in the form of not paying attention to the regulations regarding the layout, the placement of valuable objects, the dress code, the script and the lack of coordination of the protocol officers with the parties concerned indicate a lack of understanding of the procedures for implementing the protocol itself. This study uses Bidle and Thomas theory by looking at aspects, expectations, norms, forms of behavior, evaluations and actions in aspects of protocol. This study uses a qualitative approach with a descriptive method. This approach was chosen in this paper because it is able to explore in depth and detail the role of protocol in supporting the successful performance of the regional head of North Padang Lawas Regency. The results of this study indicate that the Protocol section and North Padanglawas Regency have not been able to facilitate the Regent's actions as expected. The field of protocol is able to maintain the image of the regent's government by placing the regent in accordance with his position at events held in the internal environment; However, there are shortcomings such as coordination between protocol and OPD at events held between Regional Apparatus Organizations attended by the regent. In general, the supporting factors in the implementation of protocol at the regional secretariat of the North Padanglawas Regency are, among others, leadership support, leadership initiatives, solid teamwork, cultural networks. Then the inhibiting factors in the implementation of protocol at the regional secretariat of North Padanglawas Regency, among others, the lack of human resources in the Prokopim section, Lack / Slow Coordination of the Executor of Activities (OPD) and Often implementing activities directly coordinate to the Regional Head without any information to the Prokopim section (feeling close to the leadership & feel that protocol is complicated) and lack of supporting facilities for operations such  as computers and others. the role of protocol in supporting the successful performance of the regional head of North Padang Lawas Regency is again referring to Perbup no. 53 A of 2019 concerning Organizational Position, Work Procedures and Main Duties and Functions of the Regional Apparatus of North Padang Lawas Regency and effective and efficient coordination with stakeholders related to protocol.